My child’s legacy: a mixed methods study of bereaved parents and providers’ opinions about collaboration with NICU teams in quality improvement initiatives - Annie Janvier; Sonia Dahan; Claude Julie Bourque; Ginette Mantha; Martin Reichherzer (BMJ Open)
Objective Although stakeholders’ participation in healthcare is increasingly recommended, bereaved parents are often excluded for perceived potential risks to them. The objective of this study is to describe the ongoing involvement and the perspectives of bereaved parents engaged in different types of activities in Neonatal Intensive Care Units and providers who work with them.Design/methods Mixed methods convergent analysis.Setting Canadian paediatric tertiary care university hospital.Participants All bereaved members of the resource parents group (n=8) and most providers who work with them (n=16) answered a satisfaction/needs questionnaires.Results Since 2011, eight bereaved parents were involved in a large number of activities mostly related to palliative care (research, education or clinical care initiatives). Three engaged in peer-to-peer support activities while the others preferred activities outside of clinical units and/or without direct interactions with other families. All of them reported that their participation had positive impacts, but two parents also reported a reactivation of traumatic experiences during a medical simulation activity. All participants expressed a desire for further collaboration. Motivation to contribute gravitated around two central themes: helping others and helping themselves. Many wanted to give back, help other families, improve the system and meet with providers who had cared for their child. All stated that this kind of involvement empowered them and gave meaning to their experiences. Providers and researchers all reported positive experiences, mainly due to the unique perspectives of bereaved parents who took part in their projects.Conclusion(s) With careful recruitment and supervision, some bereaved parents can become resource parents involved in different types of activities. It is important to understand the positive impacts this type of engagement can have on their healing process and to control the risks related to their participation. Research is needed to develop pertinent tools and measures to evaluate the outcomes and impacts of their participation.